Prevalence and Predictors of Self-Reported Consistent Condom Usage among Male Clients of Female Sex Workers in Tamil Nadu, India. (1st June 2014) - Rastogi, Saumya; Charles, Bimal; Sam, Asirvatham Edwin
Abstract : Clients of female sex workers (FSWs) possess a high potential of transmitting HIV and other sexually transmitted infections from high risk FSWs to the general population. Promotion of safer sex practices among the clients is essential to limit the spread of HIV/AIDS epidemic. The aim of this study is to estimate the prevalence of consistent condom use (CCU) among clients of FSWs and to assess the factors associated with CCU in Tamil Nadu. 146 male respondents were recruited from the hotspots who reportedly had sex with FSWs in exchange for cash at least once in the past one month. Data were analyzed using bivariate and multivariate methods. Overall, 48.6 and 0.8 percent clients consistently used condoms in the past 12 months with FSWs and regular partners, respectively. Logistic regression showed that factors such as education, peers' use of condoms, and alcohol consumption significantly influenced clients' CCU with FSWs. Strategies for safe sex-behaviour are needed among clients of FSWs in order to limit the spread of HIV/AIDS epidemic in the general population. The role of peer-educators in experience sharing and awareness generation must also be emphasized.